In vivo modification of the enamel pellicle and saliva resveratrol levels after use of resveratrol-containing orodispersible capsules - Levy, Flávia Mauad; Câmara, João Victor Frazão; Ventura, Talita Mendes Oliveira; Pelá, Vinícius Taioqui; Iano, Flávia [UNESP]; Araujo, Tamara Teodoro; Carvalho, Thamyris de Souza; Pavan, Nathalia Mariana [UNESP]; Ximenes, Valdecir Farias [UNESP]; Buzalaf, Marília Afonso Rabelo (Elsevier, 2024)
Objectives: To evaluate in vivo 1) the bioavailability of trans-resveratrol when administered through sublingual capsules; 2) the effect of resveratrol on the protein composition of the acquired enamel pellicle (AEP). Design: Ten volunteers received a sublingual capsule containing 50 mg of trans-resveratrol. Unstimulated saliva was then collected after 0, 30, 60, and 120 min and AEP was collected after 120 min following administration of the capsule. In the next week, the volunteers received a placebo sublingual capsule, and saliva and AEP were collected again. Saliva samples were analyzed for free trans-resveratrol using high-performance liquid chromatopgraphy (HPLC), and AEP samples were subjected to proteomic analysis (nLC-ESI-MS/MS). Results: Trans-resveratrol was detected in saliva at all the time points evaluated, with the peak at 30 min. A total of 242 proteins were identified in both groups. Ninety-six proteins were increased and 23 proteins were decreased in the Resveratrol group. Among the up-regulated proteins, isoforms of cystatins, PRPs, Mucin-7, Histatin-1, Lactotrasnferrin and Lysozyme-C were increased and the isoforms of Protein S100, Neutrophil defensins, Albumin, PRPs, and, Statherin were decreased in Resveratrol group. Conclusion: The sublingual capsule is effective at increasing the bioavailability of trans-resveratrol in saliva. Several proteins involved in important processes to maintain systemic and oral health homeostasis were identified. These proteins differently expressed due to the presence of trans-resveratrol deserve attention for future studies, since they have important functions, mainly related to antimicrobial action.
Keywords: Acquired enamel pellicle; Proteins; Proteomics; Resveratrol; Saliva